A Study of Teachers’ Strategies in Providing Feedback in English Writing Class - Nazmillah Nazmillah; Didin Nuruddin Hidayat; Maya Defianty; Anita Anita; Abdul Muin (Universitas Muhammadiyah Kalimantan Timur, 2022)
Feedback is a crucial aspect of the writing process. Feedback includes comments and suggestions to facilitate students to revise their assignments. The comments and suggestions can guide the students to revise and also support students in improving their ability, especially in writing. This study aims to find out the teacher's perspective about feedback in the writing activity in writing class and how teachers provide feedback on the student's writing activities in the writing class at an English Education Department in a university Jakarta. The method used in this research is the descriptive qualitative method. The subject of this research was the three lecturers who taught writing classes. The instruments used in this study were interviews and documents. The result shows that the role of feedback on the writing activity in writing class is important based on the data obtained. Lecturers use the combination of indirect-direct feedback and also the combination of oral and written feedback. Teachers use the feedback according to the class’s condition and the goal of the level of writing. The combination of oral and written, direct, and indirect feedback complements each other.